Antitumor effects and mechanisms of traditional Chinese medicine gamboge: A review - Zhou, Yanqing; Chen, Jialing; Zhu, Qin; Lin, Binyan (Frontiers in Pharmacology, 2025)
Traditional Chinese medicine (TCM) gamboge is a dried resin obtained from Garcinia hanburyi Hook f. For over 500 years, TCM gamboge has been used to treat scrofula, carbuncle, jaundice, furuncle, and other chronic and stubborn diseases. An increasing amount of evidence has proven the significant anticancer properties of the main active ingredients from gamboge in recent years. The ingredients of gamboge, such as gambogic acid (GA) and gambogenic acid (GNA), can inhibit tumor growth through various processes, including apoptosis induction, cell cycle arrest, tumor cell invasion and migration inhibition, and autophagy regulation. In this review, we elaborate on the role of the main active ingredients of gamboge in treating cancers. It would be enlightening to provide the possible therapeutic applications of gamboge in the clinic.